Collection of ancient Chinese cultural relics. - GUOZHEN, WANG (ATF PRESS, 2020)
In about the 11th century BC, the Shang Dynasty declined in national strength, and was destroyed by King Wu of Zhou and a capital was established in Haojing- west of what is now Xi'an, in Shanxi Province. This period is known as the Western Zhou Dynasty. Handicrafts were monopolised by the royal family and were characterised by more extensive distribution than the Shang Dynasty with more workshops and finer division of labour. Jade was only one of the many handicrafts and as something of value was very popular among royals and vassals. The pieces of importance were artefacts are: the Y3 Tomb of the Gongyu State in Baoji of Shaanxi, Guo State Tombs in Sanenxia, Luoyang, Henan Province and the Jing State tomb of Gong Yu State in Houma of Shanxi. From this period there are also bronze wares and ceramics. In this period bronze wares changed in type, shape and inscription, emblazonary and casting. Ceramics developed significantly and hand stamped hand-made pottery flourished. This book, the second in a ten-volume collection, brings to the English-speaking world a series of books from China which has been complied by an Expert Committee of the Chinese Society of Cultural Relics. There are 383 descriptions.